Volumetric soft tissue alterations in the early healing phase after peri- implant soft tissue contour augmentation with a porcine collagen matrix versus the autologous connective tissue graft: A controlled clinical trial - Schmitt, Christian; Brueckbauer, Patrick; Schlegel, Karl A.; Buchbender, Mayte; Adler, Werner; Matta, Ragai (Journal of Clinical Periodontology, 2020)
Aim This study evaluates the early volumetric changes after buccal soft tissue contour augmentation around implants with a porcine collagen matrix (CM) vs. the subepithelial connective tissue graft (SCTG) from the palate.
CRIS-Team WoS Importer:2020-11-27